ANALISI TINGKAT PROBABILITAS INVESTOR DALAM MEMBELI SAHAM SYARIAH DI PASAR MODAL DENGAN PENDEKATAN LOGISTIK - Yuspin, A. Didi (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study discusses the probability of investors buying Islamic shares in the capital market with the aim of knowing what factors influence investors in buying Islamic shares, to determine the characteristics of natural investors buying Islamic shares and to determine the probability level of investors in buying Islamic shares. The variables used are stock prices, transaction costs, return rates, risk levels and sharia compliance levels as independent variables and sharia stock purchases as the dependent variable. The research approach used is the Islamic finance approach using the logistic regression method. The data used in this research is secondary data.The results showed that the stock price had a significant effect on the purchase of sharia shares with a value of sig 0.016 0.05 and transaction costs had a significant effect on the purchase of sharia shares with a sig value of 0.017 0.05. Based on the characteristics of the stock price, namely the greater the stock price, the smaller the purchase of shares, while the characteristics of the transaction costs, namely the lower the transaction costs, the greater the purchase of shares. The probability level of investors in buying Islamic shares is 24%.